2007
DOI: 10.1080/09500830701427003
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation of niobium carbonitrides in ferrite: chemical composition measurements and thermodynamic modelling

Abstract: High-resolution transmission electron microscopy and electron-energy loss spectroscopy have been used to characterize the structure and chemical composition of niobium carbonitrides in the ferrite of a Fe-Nb-C-N model alloy at different precipitation stages. Experiments seem to indicate the coexistence of two types of precipitates: pure niobium nitrides and mixed substoichiometric niobium carbonitrides. In order to understand the chemical composition of these precipitates, a thermodynamic formalism has been de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
3

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 19 publications
1
27
0
3
Order By: Relevance
“…The inclusion of the misfit gives a significant contribution to the interface energy and must therefore be accurately accounted for in order to obtain a proper interface description. These findings will have important bearings on our ability to understand the early stage of precipitation and its pathways, 5 to thermodynamically model precipitate stability in Fe-M-X systems, 77 and to describe long-term microstructural evolution in steels. …”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of the misfit gives a significant contribution to the interface energy and must therefore be accurately accounted for in order to obtain a proper interface description. These findings will have important bearings on our ability to understand the early stage of precipitation and its pathways, 5 to thermodynamically model precipitate stability in Fe-M-X systems, 77 and to describe long-term microstructural evolution in steels. …”
Section: Discussionmentioning
confidence: 99%
“…Binary MX-type carbides have been well characterized at nanoscale by high-resolution transmission electron microscopy (HRTEM), high angle annular dark field (HAADF), electron energy loss spectroscopy (EELS), and small-angle neutron scattering (SANS) and directly giving out the platelike crystal lattice morphology and quantitative composition distribution. [11][12][13][14][15][16] With regard to multicomponent carbides, the competitive affinity of alloy elements such as V, Nb, and Ti to C is strongly influenced by cohesive energy and electron structures at the coherent interfaces between ferrous matrix and MX-type carbides. The compositional and structural evolution of transient phases is also affected by the diffusion coefficient of the carbonforming elements from the aspect of kinetic behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…6). The calculated critical radii are smaller than those measured in V-microalloyed steels, whose average size at the nose of the curve is approximately 6 nm [21]. Thus it is shown that the experimental t 0.05 time (P s curve) in Figs.…”
Section: Resultsmentioning
confidence: 77%
“…Thus it is shown that the experimental t 0.05 time (P s curve) in Figs. 1 and 2 does not exactly correspond to the start of nucleation, but that the first nuclei of precipitates form at much shorter times, in such a way that between the moment when the first precipitates form and the moment of t 0.05 corresponding to the nose of the P s curve, when the precipitates were analyzed, considerable growth of the precipitates has occurred [21].…”
Section: Resultsmentioning
confidence: 99%